2017
DOI: 10.1128/aac.00383-17
|View full text |Cite
|
Sign up to set email alerts
|

Original Chemical Series of Pyrimidine Biosynthesis Inhibitors That Boost the Antiviral Interferon Response

Abstract: De novo pyrimidine biosynthesis is a key metabolic pathway involved in multiple biosynthetic processes. Here, we identified an original series of 3-(1H-indol-3-yl)-2,3-dihydro-4H-furo[3,2-c]chromen-4-one derivatives as a new class of pyrimidine biosynthesis inhibitors formed by two edge-fused polycyclic moieties. We show that identified compounds exhibit broad-spectrum antiviral activity and immunostimulatory properties, in line with recent reports linking de novo pyrimidine biosynthesis with innate defense me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Depletion of cellular pyrimidine inhibits the replication of an array of RNA viruses, DNA viruses, and retroviruses. Interestingly, Lucas‐Hourani et al (, ) reported that pyrimidine deprivation suppresses viral growth through amplifying innate immune response, rather than depleting nucleotide precursors for viral genome replication as assumed previously (Hoffmann et al , ). Consolidating prior knowledge and the findings of genetic association studies, we hypothesized a link between GLDC and innate immunity, which may impact viral growth and underlie the genetic association of GLDC with H7N9 and severe H1N1 infection.…”
Section: Introductionmentioning
confidence: 73%
“…Depletion of cellular pyrimidine inhibits the replication of an array of RNA viruses, DNA viruses, and retroviruses. Interestingly, Lucas‐Hourani et al (, ) reported that pyrimidine deprivation suppresses viral growth through amplifying innate immune response, rather than depleting nucleotide precursors for viral genome replication as assumed previously (Hoffmann et al , ). Consolidating prior knowledge and the findings of genetic association studies, we hypothesized a link between GLDC and innate immunity, which may impact viral growth and underlie the genetic association of GLDC with H7N9 and severe H1N1 infection.…”
Section: Introductionmentioning
confidence: 73%
“…GSK983 and other inhibitors of pyrimidine biosynthesis induce expression of ISGs, the expression of which can be induced by the antiviral cytokines known as IFNs (Harvey et al, 2009; Lucas-Hourani et al, 2013; Lucas-Hourani et al, 2017). Given that ISGs mediate the antiviral effects of IFNs, it was of interest to determine how SW835 and brequinar induce ISG expression and to what extent this contributes to the antiviral effects of these compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond suppression of viral RNA synthesis, DHODH inhibitors have been demonstrated to trigger expression of ISGs, an activity that may also contribute to the antiviral effects of these compounds (Chung et al, 2016; Lucas-Hourani et al, 2013; Wang et al, 2016). Mechanistically, these compounds may not require IFN production for ISG induction but may induce ISGs through activation of the transcription factor Interferon Regulatory Factor 1 (IRF1) (Chung et al, 2016; Lucas-Hourani et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we showed that the DHODH inhibitors GAC50 and IPPA17-A04 also impair the replication of EAV, with IPPA17-A04 outperforming ribavirin and GAC50 as assessed by a higher selectivity index. It is known that Coronaviridae are inhibited by drugs targeting de novo pyrimidine biosynthesis, including HCoV-229E, MERS-CoV and SARS-CoV, and DHODH inhibitors were in the list of therapeutic options to be tested against SARS-CoV-2 [34][35][36] . Our results demonstrate that this antiviral activity extends to Arteriviridae, suggesting that pyrimidine biosynthesis inhibitors may act as pan-nidovirales inhibitors.…”
Section: Discussionmentioning
confidence: 99%